Exact relativistic plasma dispersion functions - Pavlov, S.S.; Castejon, F. (Вопросы атомной науки и техники, 2005)
On the ground of the theory of singular integrals with Cauchy kernel the exact plasma dispersion functions (PDFs) are introduced and studied. Those PDFs make more exact the weakly relativistic PDFs and generalize them on the case of arbitrary plasma temperature. На основі теорії сингулярних інтегралів з ядром Коші вводяться і досліджуються точні плазмові дисперсійні функції (ПДФ), уточнюючі слабо релятивістські ПДФ і узагальнюючі їх на випадок довільної температури. На основе теории сингулярных интегралов с ядром Коши вводятся и исследуются плазменные дисперсионные функции (ПДФ), уточняющие слабо релятивистские ПДФ и обобщающие их на случай произвольной температуры.